Artificial intelligence in writing courses: Attitudes of university instructors in Lebanon - Nicolas, Samira (Issues in educational research, 2024)
While artificial intelligence technology has been employed in different aspects of education for some time, the recent launch of generative AI tools, such as ChatGPT, has made a larger number of people aware of the advanced capabilities of these types of AI programs. Any time a new technology is introduced, the potential benefits it May have for use in the education field rely heavily on instructors' attitudes regarding those benefits and the ease, or lack thereof, with which they May be able to embrace a certain technology. Therefore, this study sought to explore the attitudes of Lebanese university writing instructors regarding the use of AI in their courses. Data were collected through a survey that was administered in the summer of 2023, with responses from 67 English writing instructors. Results revealed that overall, instructors have a neutral attitude about the use of AI in the teaching of writing, but are interested in its potential to facilitate the grading of writing assignments.